1992
DOI: 10.1002/cmr.1820040204
|View full text |Cite
|
Sign up to set email alerts
|

Optimum tip angle and relaxation delay for quantitative analysis

Abstract: For the quantitative analysis of N M R spectra, the relationship between the tip angle and the relaxation delay is examined. It is shown that the common procedure of using a small tip angle combined with a short delay is not the optimum. Instead, an angle of approximately 83" with a pulse-repetition period of 4.5 multiplied by the longest T, is the optimum procedure. However, the results obtained from this procedure are only slightly better than those obtained from the standard "90" -wait 5T," method. It is fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 4 publications
1
24
0
1
Order By: Relevance
“…All data were acquired with the sample maintained at 25jC. Selection of NMR data acquisition parameters for quantitative analysis was done according to previous studies (14). The exact resonance positions integrated for each lipid class are given below.…”
Section: Nmr Data Acquisitionmentioning
confidence: 99%
“…All data were acquired with the sample maintained at 25jC. Selection of NMR data acquisition parameters for quantitative analysis was done according to previous studies (14). The exact resonance positions integrated for each lipid class are given below.…”
Section: Nmr Data Acquisitionmentioning
confidence: 99%
“…We suspect that these conditions may not be suitable for studying a transient system. In the experiments listed in this work, we made use of the recommendations in recent literature for improving NMR analyses (Traficante, 1992;Traficante and Steward, 1994). These articles showed that a 74" tip angle, and a pulse repetition period (PR) to relaxation time ratio (PR/Tl) of 2, yield 90% integral accuracy.…”
Section: Discussionmentioning
confidence: 97%
“…Experimental spectra were collected using a 10 µs pulse‐width, which equated to a ~30° tip angle. By using a reduced tip‐angle for quantitative NMR, the required recycle delay for re‐magnetization is greatly reduced, and can be calculated using eqn , from Traficante : italicPRT1=In100italicRCcos0.5emitalicα100italicRCwhere PR = recycle delay, T 1 = target t 1 , RC = recovered magnetization (%) and α = tip angle.…”
Section: Methodsmentioning
confidence: 99%